Ukuran Optimal Pemerintah Daerah di Indonesia: Studi Kasus Pemekaran Wilayah Kabupaten/Kota dalam Era Desentralisasi - Nazara, Suahasil; Nurkholis, Nurkholis (Jurnal Ekonomi dan Pembangunan Indonesia, 2007)
This study tries to measure the optimum size of regional government (municipality/city) which will support the accomplishment of decentralization policy's objectives. The result of this study will conclude how the reformation pattern toward regional government in Indonesia should be done. The result of regressing translog and quadratic functions using cost per capita minimization approach shows the existence ofeconomy of scale from the size ofmunicipality/city's population. Using maximization approach, it is also shown that Municipality/city government expenditure is not efficient yet and has not supported the efforts to accomplish the desired development performance. With various regulations, the significant variable used in the measurement ofoptimum size is the number ofpopulation. The result of using minimization and maximization approaches show that the optimum size for municipality/city is not single (differ), between municipality and city, among each kind of per capita expenditure, and across time. Generally, the optimum and minimum size of population for municipality/city such that per capita expenditure can be minimized and such that Regional GDP per capita increases are approximately two million people. The reality of municipality/city's size which in general is relatively small compared to the optimum and minimum measurement shows the inefficiency of municipality/city government expenditure, and its ineffectiveness to support the effort to enhance the welfare ofsociety. Hence, territory extension policy performed this far, is actually worsen the accomplishment of its main objective on conducting regional government and development.